A brief review on screen lifestyle and its effect on mental patterns: Does physical activity play a role? - Lei Mengmeng; Halijah Ibrahim, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The attention towards mental health issues have gained significant attention in recent times because of lack of physical activity and intensive screen-based lifestyle. Screen based life have drastic effects on the mental health patterns and is causing serious psychological issues. A brief review consisting of 65 papers based on screen-based lifestyle and its impact on mental health patterns from past 8 years was conducted based on Scopus database. The review showed that screen-based lifestyle is related to mental health patterns, and it is a major contributor to mental health issues. Moreover, the presence of physical activity can also contribute to improve mental health patterns. Finally, this review paper contributes and provides a comprehensive understanding to the existing literature on screen-based lifestyle.